2015
DOI: 10.1016/j.wneu.2015.01.013
|View full text |Cite
|
Sign up to set email alerts
|

Neurogenic Stress Cardiomyopathy After Aneurysmal Subarachnoid Hemorrhage

Abstract: Objective Neurogenic stress cardiomyopathy (NSC) is a known complication of aneurysmal subarachnoid hemorrhage (aSAH). Detailed analyses of risk factors for its occurrence across large cohorts are relatively sparse. Methods We reviewed a consecutive group of 300 patients with aSAH, evaluating for the presence of markers of myocardial injury including EKG changes (long QT, TWI), elevated plasma troponin levels (>=0.1), and echocardiogram findings (decreased ejection fraction and wall motion abnormalities). Ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
31
0
4

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(36 citation statements)
references
References 14 publications
1
31
0
4
Order By: Relevance
“…In a retrospective study of 46 SAB-triggered TTS patients the risk for ischemic stroke was increased among those with reduced systolic function [7]. In a study of 300 patients with SAB, 45 (15%) had neurogenic stress cardiomyopathy [8]. Risk factors for TTS were high Hunt-Hess-score (HHS), smoking, and old age [8].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In a retrospective study of 46 SAB-triggered TTS patients the risk for ischemic stroke was increased among those with reduced systolic function [7]. In a study of 300 patients with SAB, 45 (15%) had neurogenic stress cardiomyopathy [8]. Risk factors for TTS were high Hunt-Hess-score (HHS), smoking, and old age [8].…”
mentioning
confidence: 99%
“…In a study of 300 patients with SAB, 45 (15%) had neurogenic stress cardiomyopathy [8]. Risk factors for TTS were high Hunt-Hess-score (HHS), smoking, and old age [8]. In a study of 135 SAB patients undergoing echocardiography TTS was found in 25 (18.5%) [9].…”
mentioning
confidence: 99%
“…NSM is characterised by reversible left ventricular dysfunction and is hypothesised to result from a combination of hypothalamic dysfunction, catecholamine surges and myocardial perivascular lesions 16. There is no clear definition of diagnosis, but it resolves around severe cardiac dysfunction which may include elevation of troponin, ejection fraction <55% or significant ECG abnormalities17 and results in higher mortality and morbidity rates18 in patients after SAH. There is no specific therapy, and these patients undergo cardiorespiratory support measures until the cardiac dysfunction improves.…”
Section: Discussionmentioning
confidence: 99%
“…Literatürde NSK; "nörojenik afallamış miyokard" (neurogenic stunned myocardium), "nörojenik kardiyak afallama" (neurogenic cardiac stunning), "nörokardiyojenik hasarlanma" (neurocardiogenic injury) olarak da adlandırılmaktadır (4,8). Altta yatan patofizyolojiyi daha doğru bir şekilde yansıttığı için, NSK terimi daha yaygın olarak kullanılmaktadır (8).…”
Section: Subaraknoid Kanamanın Kalbe Etkileriunclassified
“…Kalp debisini ve ortalama arter basıncını artırmak ve dolayısıyla serebral perfüzyon basıncını düzeltmek için kompansasyon mekanizmaları devreye girer. En önemli kompansasyon mekanizması olan sempatik aktivasyonun, NSK patofizyolojisinde rol oynadığı düşünülmektedir (5,8). NSK'nin patofizyolojisinde katekolaminlerin suçlanması görece yeni bir bilgidir.…”
Section: Subaraknoid Kanamanın Kalbe Etkileriunclassified